Analysis of Determinants of Hearing Health Based on Audiometric Examination in Boat Miners - irawati, Ice; Sari, Chinta Yolanda; Maulina, Diina (Sarana Ilmu Indonesia (Salnesia), 2025)
Boat miners at Sagulung Port, Batam City face the risk of high noise exposure from boat engines that can affect hearing health. This study analyzed the determinants of hearing loss among 30 boat miners at Sagulung Port, Batam City, using a quantitative analytic cross-sectional design. Through audiometric examinations and noise measurements, the research found significant relationships between hearing loss and age (p-value = 0,015; PR = 4,24), exposure duration (p-value <0,001; PR = 5,34), and noise intensity (p-value <0,001; PR = 8,5). Multivariate and Poisson regression analyses identified noise intensity as the dominant determinant (p-value <0,001; PR = 0,926), revealing that subjects exposed to noise within safe Threshold Limit Values (NAB) had a 7,4% lower prevalence of hearing loss than those exposed to unsafe levels. Conversely, the length of service did not show a significant individual relationship (p-value = 0,216; PR = 1,50). The study concludes that high occupational noise significantly impacts hearing health, leading to recommendations for mandatory ear protection, regulated working hours, and targeted safety education to mitigate permanent auditory damage among boat miners.